Testing the Tenacity of Small Ruminant Lentiviruses In Vitro to Assess the Potential Risk of Indirect Fomites’ Transmission - Maksym Samoilenko; Vitalii Nedosekov; Giuseppe Bertoni (Viruses)
In 2011–2013, we isolated and characterized small ruminant lentiviruses (SRLVs) from two flocks, one of goats and the other of sheep, that had never been in direct contact. Phylogenetic analysis of these viruses indicated a common origin, which led us to hypothesize indirect transmission of these viruses between the two flocks. Since, to our knowledge, there are no published data on the tenacity of these viruses, we started this work. In the first part, we monitored the loss of infectivity of two prototypic SRLV strains, MVV 1514 and CAEV-CO, over time, in liquid suspension. As expected, the suspensions stored at 4 °C better preserved the infectivity of the viruses. Additionally, viruses resuspended in milk, the medium mirroring the in vivo situation, proved more tenacious than those maintained in a cell culture medium. These viruses, subjected to harsh treatments such as drying and resuspending, partially maintained their replication capacity. After an immediate loss of nearly 1 log10 TCID50 immediately after desiccation, the viruses maintained their replication capacity for at least three weeks when desiccated in milk. These results suggest that fomites, clothing, or pastures contaminated with secretions or milk from infected animals might mediate the infection of animals independently of direct contact.